Vitamin D3 mediates amelioration of ulcerative colitis via the TRPV1-MAPK signaling pathway - Zhao, Keke; Li, Jian; Asai, Yersen; Zhang, Longxiang; Hu, Ziying; Gao, Hongliang (Frontiers in Immunology, 2026)
IntroductionUlcerative colitis (UC), known as a complex inflammatory bowel disease, whose pathogenesis has not been fully clarified. The Transient Receptor Potential Vanilloid 1 (TRPV1), along with its downstream Mitogen-Activated Protein Kinase (MAPK) pathway, are vital in regulating inflammation. However, it remains unclear whether vitamin D3 (VD3) exerts a protective effect by regulating this signaling pathway.MethodsThis study investigated the TRPV1-MAPK pathway in colon tissues from UC patients and in 3% Dextran Sulfate Sodium (DSS)-induced rodents. In vivo experiments were conducted to evaluate the effects of VD3 intervention on disease phenotype, including body weight, Disease Activity Index (DAI), colon length, histological damage, and epithelial cell apoptosis. The study analyzed gene and protein expression levels of TRPV1 and key molecules in the MAPK pathway, and immunofluorescence co-localization was used to assess TRPV1 expression on macrophages. Serum calcium ion (Ca2+) levels were measured to explore the modulation of calcium homeostasis.ResultsThe TRPV1-MAPK pathway was remarkably upregulated in UC patients and DSS-induced rodents, manifested as upregulated expression levels of TRPV1, phosphorylated p38 (p-p38), and phosphorylated Extracellular Signal-Regulated Kinase (p-ERK). VD3 intervention significantly ameliorated disease phenotype, effectively alleviated weight loss, increased DAI, colon shortening, and tissue damage in mice, and reduced epithelial cell apoptosis. VD3 treatment significantly downregulated both gene transcription and protein expression of TRPV1. Immunofluorescence co-localization confirmed that VD3 reduces TRPV1 expression on macrophages. Alterations in serum Ca2+ levels suggested that VD3 may influence TRPV1-mediated calcium influx by modulating calcium homeostasis, thereby suppressing MAPK pathway activation. Consequently, this regulatory cascade led to a significant decrease in pro-inflammatory cytokines, including Interleukin-1Beta (IL-1β), Interleukin-6 (IL-6), and Tumor Necrosis Factor-Alpha (TNF-α), and concurrently restored intestinal barrier function by upregulating the expression of Occludin and Mucin2 (Muc2).DiscussionThis study elucidates a protective role of VD3 in UC, whereby it coordinately regulates immune responses and barrier function via the TRPV1-MAPK signaling pathway, providing a novel theoretical and experimental foundation for VD3-based therapy for UC.